Estudio de Factibilidad para la creación de una Empresa de Capacitación para Establecimientos Hoteleros en la Ciudad de Puyo - Pucuna Chango, Aracely Cecibel (2013)
The Researh carried out a feasibility study for the creation of a company training establishment for hoteliers in the city of Puyo, through market research has allowed us to determine the need for training the staff working in the hotel sector, in the same way being able to learn that the project is feasible, due to the reception that would have to be CAHO S.A., the first private company dedicated to this type of service. Research is carried out theoretical-conceptual that allowed knowing as has been the history around the hotel service, which has been their foundation to open them, trajectory, and services offered, and with this understanding in turn what level of training has been done so far. Based on the marketing of social networks, promotions, worth of mouth marketing, among others, will be one of the tactics that will be used to achieve the service contract. The company would be located in a strategic place and easy to reach, composed of qualified personnel to their jobs, with a General Manager, a Trainer, a Sales person, and a Receptionist. Thereby achieving cover needs, enhance knowledge and benefit the hotel industry in the city of Puyo, allowing guests feel important during their stay in the hotel of your choice. The investment for this project is $ 10 006,91 U.S. dollars, amount which will be recovered in a time span of two years approximately, the investment that is required will be distributed in fixed assets, deferred tax assets and human capital, funded by partners that will provide the 30% and by the National Financial Corporation with 70% to five years. Obtaining the Net Present Value $ $ 14 371,89 U.S. the Internal Rate of Return 51 per cent for every dollar invested in the project will provide a profit of $ 1,44 U.S. dollars in such a way that the recovery of the investment will be achieved within the estimated time